Biomass Valorization: Sustainable Methods for the Production of Hemicellulolytic Catalysts from Thermoanaerobacterium thermostercoris strain BUFF - Ilaria Finore (MDPI AG, 2021)
Processing and selection of fruits and vegetables generate high quantities of wastes that represent an economic and environmental issue for the agroindustry sector. According to the so-called “biorefinery” approach, this biomass can be exploited for the recovery of value-added molecules. In this study, the residues of industrial processing of tomato (Lycopersicon esculentum variety “Hybrid Rome”), fennel (Foeniculum vulgare), potato (Solanum tuberosum) and carrot (Daucus carota) were used as sole carbon sources to support cheap and sustainable microbial growth as well as the production of secondary metabolites (hydrogen and ethanol) by Thermoanaerobacterium thermostercoris strain BUFF, a thermophilic anaerobic microorganism isolated from buffalo-dung compost. Moreover, the use of hemicellulolytic enzymes of T. thermostercoris was assayed in the bioconversion reaction of the polymer fraction extracted from the rhizome of giant reed (Arundo donax) and of the leaves and stems of cardoon (Cynara cardunculus), dedicated non-food crops employed in energy supply.